(NsOWREMENNAQ IMPROWIZACIQ PRAKTI^ESKIJ KURS DLQ FORTEPIANO(B.s (NmETODIKA(B.. (Nu^EBNOE POSOBIE(B.s - (NsTOLQR r(B. (Ns(B.s ((NmOSKWAs (NpLANETA MUZYKIs, 2020)
(NkNIGA BUDET INTERESNA DVAZOWYM ISPOLNITELQM(B.s
Keywords: (NmETODIKAs